Antioxidant Activity and Total Phenol Content of Ethanol Extract Takokak Fruit (Solanum torvum) - Rahman, Nur; Marliyati, Sri Anna; Damanik, Muhammad Rizal Martua; Anwar, Faisal (Pakistan Journal of Nutrition, 2013)
Takokak is a potential source of antioxidants for scavenger free radical. This study carried out to examines the affect of ethanol concentration to the yield extract, total phenol and antioxidants activity in variety maturity stage takokak (Solanum torvum). Research design was experiment laboratorium. The yield was calculated by comparing the weight of extract with baseline weight, phenol assay using the Folin-Ciocalteu reagent and antioxidants activity assay using DPPH method. The result showed that ethanol concentration ethanol 70 and 96% was significantly affected the yield extract (p = 0.000) and (p = 0.000). Concentration 70 and 96% did not significantly affect on level phenol (p = 0.056) and (p = 0.342). Concentration 70% was significantly affected antioxidant activity (p = 0.014), but concentration 96% was not significanlyt affected (p = 0.114) on the variety maturity stage of Solanum torvum. The best extracts was ethanol extract 70% old dried mature fruits.